Global aviation alliances : An effect of cooperation on individual performance of airlines - Vasilyev, Mikhail; Zouhar, Jan, 1982-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
In recent years such constellations, like global aviation alliances were formed and they have been developing a lot. They heavily affect the airline market. Using the data from annual reports of 11 different airlines on operational and financial performances, I run a panel data model. The main objective is to understand the effect of global aviation alliance membership on the performance of airlines - revenue and passenger flow in particular. Using different methods and models, such as fixed effects and first differences based on panel data I was not able to document a significant result. Therefore, I could not conclude that it is either beneficial or not in terms of revenue and amount of passengers for airlines to enter an alliance. However, it is not the only thing to take into account and there is more to be researched in this industry, as well as a possibility to improve this research.
Vedoucí práce: Jan Zouhar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses